2021
DOI: 10.1038/s41416-021-01319-8
|View full text |Cite
|
Sign up to set email alerts
|

Determining lines of therapy in patients with solid cancers: a proposed new systematic and comprehensive framework

Abstract: The complexity of neoplasia and its treatment are a challenge to the formulation of general criteria that are applicable across solid cancers. Determining the number of prior lines of therapy (LoT) is critically important for optimising future treatment, conducting medication audits, and assessing eligibility for clinical trial enrolment. Currently, however, no accepted set of criteria or definitions exists to enumerate LoT. In this article, we seek to open a dialogue to address this challenge by proposing a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…Any anticancer therapy (chemotherapy, biologics, targeted therapy, immunotherapy, and hormonal therapy) entered into EHR treatment plans was defined as an eligible LoT, consistent with a recently published framework. 30 Injectable and selected oral hormonal therapies for prostate and breast cancer were not included. Finally, to define a TDP, we identified a visit within 30 days before the LoT start date with values for required features.…”
Section: Methodsmentioning
confidence: 99%
“…Any anticancer therapy (chemotherapy, biologics, targeted therapy, immunotherapy, and hormonal therapy) entered into EHR treatment plans was defined as an eligible LoT, consistent with a recently published framework. 30 Injectable and selected oral hormonal therapies for prostate and breast cancer were not included. Finally, to define a TDP, we identified a visit within 30 days before the LoT start date with values for required features.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, many patients affected by advanced malignancy receive sequential anti-cancer therapies, which may include chemotherapy, immunotherapy, targeted therapy, endocrine therapy, or a combination of them. The complexity requires strict criteria to define and enumerate the sequential lines of therapy uniformly across solid malignancies (12). From a mechanistic point of view, recent high-throughput sequencing studies and quantitative modeling approaches have revealed extensive intratumor heterogeneity and highly dynamic tumor clonal evolution under the selective pressure exerted by drug treatments (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…From NAMI-A to KP1019, KP1339, and TLD1433, the development of ruthenium antitumor drugs is moving from monotherapy to combination therapy. 31 Combination therapy for cancer includes combination of multiply drugs and the combination of multiple modalities [32][33][34] , including chemotherapy, radiotherapy, photodynamic therapy, photothermal therapy, immunotherapy and gene therapy, etc. 3,[35][36][37] .…”
Section: Introductionmentioning
confidence: 99%